Case report: Novel transtemporal transverse sinus decompression surgery to alleviate transverse sinus stenosis in a pulsatile tinnitus patient with restricted bilateral venous outflow - Hsieh, Yue-Lin; Wang, Wuqing (Frontiers in Surgery, 2023)
Transverse sinus (TS) stenosis is commonly found in individuals with venous pulsatile tinnitus (PT). While PT can be addressed through endoluminal or extraluminal methods, the former has shown promise in alleviating symptoms associated with increased intracranial pressure. This study explores the potential of extraluminal method to alleviate TS stenosis and eliminate PT caused by sigmoid sinus diverticulum. A 31-year-old male patient presenting with left-sided PT, attributed to a large, peduncled sigmoid sinus diverticulum (SSD) along with severe ipsilateral TS stenosis and contralateral TS hypoplasia, underwent extraluminal TS decompression surgery following sigmoid sinus wall reconstruction under local anesthesia. Postoperative CT and MR angiography revealed a significant increase in TS lumen from 0.269 to 0.42 cm 2 (56.02%) two years after surgery. Cervical Doppler ultrasound demonstrated a 36.07% increase in ipsilateral outflow volume to 16.6 g/s and a 77.63% increase in contralateral outflow volume to 1.35 g/s. In conclusion, this pioneering study showcases the potential of transtemporal TS decompression surgery in creating space for adaptive expansion of the TS lumen. However, the procedure should be reserved for individuals with severely compromised venous return.